2014
DOI: 10.1016/j.ces.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatory rise of microbubble swarm along a vertical wall

Abstract: Based on the experimental finding that microbubble swarms dramatically promote heat transfer from a vertical heated wall, despite their potentially adiabatic nature, tests of microbubble fluid mechanics in the isothermal state are performed to clarify the unique motion characteristics of microbubble swarms. At constant bubble flow rate, the microbubble swarm shows a significant pulsatory rise along a vertical flat wall, particularly for small bubbles. Particle tracking velocimetry applied to the microbubbles s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Zimmerman et al [12] studied the trade-off between heat transfer and evaporation at the microbubble interface both experimentally and by computational modeling, and found that the vapor temperature decreased with increasing contact time. The present authors' group, Kitagawa and Murai [13], investigated the motion characteristics of microbubble swarms ascending close to a vertical wall, and clarified that under specific conditions of bubble size and bubble flow rate, a two-way interaction between the microbubbles and the liquid flow self-excites the pulsation during their co-current rise. As a model of microbubble cluster, Murai et al [14] measured the rheology of liquid including spherical bubbles, and found that the effective viscosity jumped up by three orders of magnitude higher than the original carrier phase viscosity at a local volume fraction of bubbles of approximately 50 % (i.e., superficial freezing effect of microbubble clusters in shear flows).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Zimmerman et al [12] studied the trade-off between heat transfer and evaporation at the microbubble interface both experimentally and by computational modeling, and found that the vapor temperature decreased with increasing contact time. The present authors' group, Kitagawa and Murai [13], investigated the motion characteristics of microbubble swarms ascending close to a vertical wall, and clarified that under specific conditions of bubble size and bubble flow rate, a two-way interaction between the microbubbles and the liquid flow self-excites the pulsation during their co-current rise. As a model of microbubble cluster, Murai et al [14] measured the rheology of liquid including spherical bubbles, and found that the effective viscosity jumped up by three orders of magnitude higher than the original carrier phase viscosity at a local volume fraction of bubbles of approximately 50 % (i.e., superficial freezing effect of microbubble clusters in shear flows).…”
Section: Introductionmentioning
confidence: 87%
“…Then the bubble velocity vector is computed using the three-time-step tracking PTV algorithm (e.g., Kitagawa et al [28]). The details of the procedure used to estimate the bubble velocity were previously given by Kitagawa and Murai [13]. The uncertainty in the bubble velocity associated with bubble centroid detection is estimated to be 1.1 mm/s, which corresponds to approximately 2 % of the mean rise velocity of microbubbles for the Type C surface.…”
Section: Bubble Velocity Measurementmentioning
confidence: 99%
“…Moreover, this instability might cause the wavy shape of the bubble curtain's edge. A comparable instability of the upwards directed flow might as well have played a role in the formation of the bubble clouds observed by Kitagawa and Murai (2014). Figure 7 illustrates the mean wall parallel velocity profiles for all investigated configurations.…”
Section: Liquid Phase Velocities Near the Cathodementioning
confidence: 93%
“…The mass and heat transfer enhancement from vertical walls to liquids due to the addition of ascending gas bubbles has long been recognized (Farmer 1885; Roald and Beck 1951;Kölbel et al 1958). A recent overview is provided by Vogt and Stephan (2015) for mass transfer and by Kitagawa and Murai (2014) for heat transfer enhancement. However, detailed measurements resolving the behavior of single bubbles are relatively scarce.…”
Section: Introductionmentioning
confidence: 97%
“…In this figure, ″TPF″ and ″SPF″ represent two-phase and single-phase flows, respectively. Results for the 2-D simulation of single-phase natural convection, performed by our group [38], are also shown in Fig. 7.…”
Section: Local Temperature In Liquid Phasementioning
confidence: 99%